2013
DOI: 10.1103/physrevlett.110.222001
|View full text |Cite
|
Sign up to set email alerts
|

Determination of theX(3872)Meson Quantum Numbers

Abstract: The quantum numbers of the Xð3872Þ meson are determined to be J PC ¼ 1 þþ based on angular correlations in B þ ! Xð3872ÞK þ decays, where Xð3872Þ ! þ À J=c and J=c ! þ À . The data correspond to 1:0 fb À1 of pp collisions collected by the LHCb detector. The only alternative assignment allowed by previous measurements J PC ¼ 2 Àþ is rejected with a confidence level equivalent to more than 8 Gaussian standard deviations using a likelihood-ratio test in the full angular phase space. This result favors exotic expl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
155
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 364 publications
(159 citation statements)
references
References 29 publications
4
155
0
Order By: Relevance
“…The 2003 discovery by the Belle experiment [7] of the Xð3872Þ in the channel B AE → K AE Xð→ π þ π − J=ψÞ was the first candidate exotic meson in which heavy flavor quarks participate. This state was subsequently confirmed in several production and decay modes by ATLAS [8], BABAR [9], BES III [10], CDF [11], CMS [12], D0 [13] and LHCb [14] Collaborations. Several additional four-quark candidate exotic mesons have since been found, though in many cases not all experiments have been able to confirm their existence.…”
Section: Introductionmentioning
confidence: 89%
“…The 2003 discovery by the Belle experiment [7] of the Xð3872Þ in the channel B AE → K AE Xð→ π þ π − J=ψÞ was the first candidate exotic meson in which heavy flavor quarks participate. This state was subsequently confirmed in several production and decay modes by ATLAS [8], BABAR [9], BES III [10], CDF [11], CMS [12], D0 [13] and LHCb [14] Collaborations. Several additional four-quark candidate exotic mesons have since been found, though in many cases not all experiments have been able to confirm their existence.…”
Section: Introductionmentioning
confidence: 89%
“…2.1.2.1) and decays into D * 0D0 , D 0D0 π 0 , γJ/ψ, γψ(3686), and ωJ/ψ with ω decaying into π + π − π 0 . Its quantum numbers have been studied by Belle, BaBar and CDF, and determined to be I G J PC = 0 + 1 ++ by the recent LHCb experiment [70], as shown in Fig. 4.…”
Section: The Charmonium-like Xyz Statesmentioning
confidence: 99%
“…Both BABAR and Belle observed the Xð3872Þ → γJ=ψ decay process, which ensures that the Xð3872Þ is a C-even state [5,6]. The CDF and LHCb experiments determined the spin parity of the Xð3872Þ to be J P ¼ 1 þ [7,8], and CDF also found that the π þ π − system was dominated by the ρ 0 ð770Þ resonance [9]. Because of the proximity of its mass to theDD Ã mass threshold, the Xð3872Þ has been interpreted as a candidate for a hadronic molecule or a tetraquark state [10].…”
mentioning
confidence: 99%